1995
DOI: 10.2307/2061689
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Character of Stepfamilies: Implications of Cohabitation and Nonmarital Childbearing

Abstract: Divorce, nonmarital childbearing, and cohabitation are reshaping family experience in the United States. Because of these changes, our traditional definitions of families decreasingly capture of the social units of interest. We have noted how a significant proportion of officially defined single-parent families actually are two-parent unmarried families. The present paper expands on this perspective with respect to stepfamilies. We must broaden our definition of stepfamilies to include cohabitations involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0
4

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(179 citation statements)
references
References 29 publications
1
174
0
4
Order By: Relevance
“…In doing so, we misrepresent the experience of children who live with their father or other relatives during childhood. Earlier studies have repeatedly demonstrated the robustness of this procedure (Bumpass, Raley, and Sweet 1995;Bumpass and Sweet 1989;Raley and Wildsmith 2001). Table 1 compares the background characteristics of the NSFG V and NSFG VI (female) samples-here, as elsewhere, the estimates are weighted (see 3.2).…”
Section: B 32 Methodsmentioning
confidence: 91%
“…In doing so, we misrepresent the experience of children who live with their father or other relatives during childhood. Earlier studies have repeatedly demonstrated the robustness of this procedure (Bumpass, Raley, and Sweet 1995;Bumpass and Sweet 1989;Raley and Wildsmith 2001). Table 1 compares the background characteristics of the NSFG V and NSFG VI (female) samples-here, as elsewhere, the estimates are weighted (see 3.2).…”
Section: B 32 Methodsmentioning
confidence: 91%
“…This paper has not addressed the full range of complexity among the stepfamilies, either. The analysis only applies to marriages, whereas a nontrivial proportion of stepfamilies are indeed cohabiting unions (Bumpass, Raley, and Sweet 1995). Given its higher instability and shorter duration, it is implausible that childbearing behaviors in cohabitating unions will follow the same institutionalization process.…”
Section: Discussionmentioning
confidence: 99%
“…I am grateful as well to Gunnar Andersson and Gerda Neyer for inviting me to contribute to this volume in Jan's honor, and also to them for their help and ideas. Goode, 1993;Bumpass, Raley, and Sweet, 1995;Goldscheider et al, 2000. 2. van Amersfoort, 1999, accuses European demographic scholarship of having an "ostrich" mentality, ignoring the phenomenon of immigration that is unfolding all around. However, in the 1990s, European population literature began to draw special attention to the labor contributions of international migration versus the competition immigrants could pose to longstanding residents and citizens, and later the potential costs and gains of raising their children.…”
Section: Acknowledgementsmentioning
confidence: 99%